Consulting Services Manual 2006 : A Comprehensive Guide to the Selection of Consultants at the World Bank - World Bank (Washington, DC, 2012)
The second edition of the Consulting Services Manual provides details guidance to borrowers, World Bank staff, and consultants on the application of mandatory provisions of the Consultant Guidelines, the Standard Request for Proposal (SRFP), and other policies, and provides advice on the application of professional best practices on non-mandatory aspects of working with the World Bank.